MOF-derived BC-Co@NC nanoarchitectures coupled with FS-DVC algorithm for resolving overlapping voltammetric signals of catechol/hydroquinone isomers - Zeng, Xiangrong; Xiao, Hongyu; Lei, Yaxuan; Ye, Sifei; Liu, Peng; Kong, Zhuohua; Wen, Yangping; Tan, Guixia; Gong, Xia; Li, Mingfang (Electrochimica acta, 2025)
•Electrochemical discrimination of o-/p-dihydroxybenzene isomer was realized by derivative voltammetry.•A new sensing paradigm driven by material-algorithm dual-engine was established.•Metal-nonmetal co-doped carbon via topologically oriented carbonization was developed. The simultaneous electrochemical detection of catechol (CC) and hydroquinone (HQ) isomers is hindered by overlapping voltammetric signals, creating a persistent sensitivity-selectivity-accuracy paradox. Herein, we present a synergistic sensing platform integrating BC-Co@NC nanoarchitectures (engineered via topotactic carbonization to form 3D hierarchical pores with atomically dispersed Co-N4 sites) and a first- and second-derivative voltammetry cascade (FS-DVC) optimized by Savitzky-Golay algorithm. This dual-engine strategy achieves 152 mV interpeak separation, ultra-low limits of detection (0.09 nM for CC, 0.12 nM for HQ), a linear range spanning four orders of magnitude (0.3-500 μM), and robust performance in environmental matrices (95.2-99.1% recoveries in agricultural water/soil). This work establishes a new paradigm for electrochemical isomer discrimination through the synergistic fusion of tailored material design and advanced signal mathematics.